2015
DOI: 10.1186/s12888-015-0649-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression among adolescents living with HIV in Malawi

Abstract: BackgroundPrior research suggests that a high prevalence of depression, with a detrimental impact on treatment outcomes exists among HIV-infected youth. Data on potential risk factors of depression among HIV-infected youth in sub-Saharan Africa are scarce. This cross-sectional study aimed to identify contributory/protective factors associated with depression in Malawian adolescents 12–18 years old living with HIV.MethodsDepression was measured by a validated Chichewa version of the Beck Depression Inventory ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
148
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(174 citation statements)
references
References 47 publications
(51 reference statements)
19
148
6
Order By: Relevance
“…In a study of 162 HIV-infected children and adolescents in Kenya, 49% were reported to have at least one psychiatric diagnosis or suicidality, with anxiety disorders most common (32.3%), followed by major depressive disorder (17.8%) [28]. A cross-sectional study of 562 HIV-infected adolescents from Malawi found a depression prevalence of 18.9% [29,30]. Within another study in Rwanda examining 100 HIV-infected children ages 7–14 years, the prevalence of depression reported was 25% [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 162 HIV-infected children and adolescents in Kenya, 49% were reported to have at least one psychiatric diagnosis or suicidality, with anxiety disorders most common (32.3%), followed by major depressive disorder (17.8%) [28]. A cross-sectional study of 562 HIV-infected adolescents from Malawi found a depression prevalence of 18.9% [29,30]. Within another study in Rwanda examining 100 HIV-infected children ages 7–14 years, the prevalence of depression reported was 25% [31].…”
Section: Resultsmentioning
confidence: 99%
“…One study found male sex to be associated with a greater risk of depression than female sex in Kenya [28], while another found female sex to be associated with higher BDI-II scores in Malawi [30]. Another study found depression rates to be higher among HIV-infected adolescent females than males in Rwanda, but this difference was not significant [31], while another found no significant association between sex and suicidal ideation or behaviour in Rwanda [35].…”
Section: Resultsmentioning
confidence: 99%
“…Both measures have been validated in diverse settings and cultures [32][33][34][35][36][37]. A locally validated and culturally adapted Chichewa version of the BDI was used [28,29]. The Cronbach's alpha for the BDI was 0.80 [28,29].…”
Section: Depressionmentioning
confidence: 99%
“…Antiretroviral treatment (ART) adherence may be compromised when an adolescent also has to be responsible for their health, food security, livelihood, and shelter. Stigma around HIV from peers at school or in their community may also compromise ART adherence, as ALHIV without peer support can feel isolated . Disclosing HIV status may be difficult, creating a barrier to developing supportive friendships and peer relationships.…”
Section: Introductionmentioning
confidence: 99%